Safety of antiandrogen therapy for treating prostate cancer. (November 2014) - Ricci, Francesco; Buzzatti, Giulia; Rubagotti, Alessandra; Boccardo, Francesco
<x xml:space="preserve">Abstract</x> Introduction: Antiandrogens are a treatment option in patients with prostate cancer, given either in combination with androgen deprivation or, in selected cases, as monotherapy. New-generation antiandrogens have been recently introduced in clinical practice (enzalutamide) or are under evaluation in clinical trials (ARN-509). Areas covered: This review elucidates the safety profile of antiandrogens, in particular focusing on the tolerability profile of each drug either when employed in combination with castration or as monotherapy, in hormone-naive or in castration-resistant patients. Expert opinion: Non-steroidal antiandrogens are widely used in the management of hormone-sensitive disease in combination with luteinizing hormone-releasing hormone agonists or in patients failing front-line treatment with androgen-deprivative maneuvers. In selected patients, non-steroidal antiandrogen monotherapy appears to yield comparable results as castration. Novel non-steroidal antiandrogens have been investigated with promising results in castration-resistant prostate cancer. Beyond the safety profile specific to any individual compound, increased testosterone and 17β-estradiol levels are commonly observed during antiandrogen monotherapy, leading to gynecomastia and breast pain. The safety profile of old and novel antiandrogens should be taken into account by clinicians in decision making and in selecting the most suitable patients. Beyond patient selection, full clinical evaluation of patient co-morbidities that might affect the drug tolerability and clinical monitoring are anyway required.